2006
DOI: 10.1099/mic.0.28723-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a cytochrome bcc–aa 3 interaction in the respiratory chain of Mycobacterium smegmatis

Abstract: Spectroscopic analysis of membranes isolated from Mycobacterium smegmatis, along with analysis of its genome, indicates that the cytochrome c branch of its respiratory pathway consists of a modified bc 1 complex that contains two cytochromes c in its c 1 subunit, similar to other acid-fast bacteria, and an aa 3-type cytochrome c oxidase. A functional association of the cytochrome bcc and aa 3 complexes was indicated by the findings that levels of detergent sufficient to completely disrupt isolated membranes fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 33 publications
4
70
0
Order By: Relevance
“…[Matsoso et al, 2005;Megehee et al, 2006;Kim et al, 2015]. To provide further evidence in support of this suggestion, we separated protein complexes in solubilized membrane fractions derived from spores (Fig.…”
Section: Evidence For Dissociation Of the Bcc-aa 3 Supercomplex Into mentioning
confidence: 77%
See 1 more Smart Citation
“…[Matsoso et al, 2005;Megehee et al, 2006;Kim et al, 2015]. To provide further evidence in support of this suggestion, we separated protein complexes in solubilized membrane fractions derived from spores (Fig.…”
Section: Evidence For Dissociation Of the Bcc-aa 3 Supercomplex Into mentioning
confidence: 77%
“…1). Early studies performed with C. glutamicum, and more recently with M. tuberculosis and M. smegmatis, have revealed that these two large enzyme complexes form a bcc-aa 3 supercomplex Megehee et al, 2006;Kim et al, 2015;Kao et al, 2016], which is necessary if a soluble c-type cytochrome component is lacking [Niebisch and Bott, 2001;Sakamoto et al, 2001;Sone et al, 2001].…”
mentioning
confidence: 99%
“…We also observed that expression of ald was increased by 27% relative to that of the control when M. smegmatis cells were treated with 500 M CN Ϫ (data not shown). There are two functional terminal oxidases in the ETC of M. smegmatis, aa 3 cytochrome c oxidase and bd quinol oxidase (46,47). The activity of aa 3 cytochrome c oxidase is inhibited by NO and CN Ϫ , while bd-type quinol oxidase is insensitive to CN Ϫ (46).…”
Section: Discussionmentioning
confidence: 99%
“…A candidate of interest in the cytochrome caa 3 is the unusually acidic patch that was noted when the operon encoding the complex was first cloned and sequenced (17). This acidic domain is predicted to be near the region of subunit II just above where the pumped protons are modeled to emerge (50,51). Also of interest will be the roles of specific membrane lipids, especially cardiolipin (8), and additional respiratory chain components in supercomplex formation or proton transfer.…”
Section: Stepr Studies Of Spin-labeled Cytochrome Caa 3 Embedded In Pmentioning
confidence: 99%